(untitled) (Voice of History, 2025)
This paper presents a comparative analysis of the fundamental rights enshrined in the Constitution of Nepal 2072 BS (2015 AD) and the Constitution of Nepal 2019 BS (1963 AD). Through a detailed examination of both constitutional texts, the evolution of fundamental rights is analyzed in the context of socio-political changes, legal frameworks, and the practical implementation of these rights. The research identifies the major developments in fundamental rights protection over the years, assesses the legal mechanisms in place, and evaluates the impact of constitutional provisions on Nepalese society. The findings underscore the significant advancements and ongoing challenges in ensuring the full realization of fundamental rights, with particular attention to the role of the judiciary, legislature, and executive in enforcing these rights. The paper is presented inductively and choice of methodology is qualitative.